The Living Arrangements of Older Persons in Rural and Urban Settings of Akuapim North District - Ayisi, E. (University of Ghana, 2013)
In today’s changing economic, political, demographic, and environmental context, the living arrangements of the rapidly growing older population warrant disproportionate policy attention. Lack of support by the state coupled with economic hardship and decreasing kin or family availability implies that older persons are more and more expected to find their own means of support develop their own strategies and depend on their own resources. This study uses a descriptive approach in its quest to understand the living arrangements of older persons, and its association with the general health status of older persons in the Akuapim North District of Eastern Region. In this survey, questionnaire has been used to collect the data. Frequency tables and charts have been used to present the data. The results of this study indicated that living with spouse was the most common type of living arrangement for older persons living in the rural areas of Akuapim North District. On the contrary, skipped-generation household was the common type of living arrangement for older persons in urban areas of Akuapim North District. Co-residence with grandchildren and or without other extended kin, and living specifically with spouse, although cannot certainly guarantee better health status, was associated with better life satisfaction compared to living alone or solitary living. Part of this life satisfaction is due to the effect of the social support function which is largely related to co-residence with spouse or other family members, such as children and grandchildren. The findings of this study revealed that living arrangements play a significant role in the life satisfaction and fulfillment of older persons in Akuapim North District. One can therefore, precisely assume that social support is a vital determinant of life satisfaction and fulfillment.
Thesis (MA) - University of Ghana, 2013